Psikoedukasi dan Konseling Mandiri sebagai Strategi Penurunan Ansietas Remaja Young Caregiver - Anugerah, Shelany; Wardaningsih, Shanti (Pustaka Galeri Mandiri, 2025)
Adolescents who play the role of primary caregivers for parents with chronic illnesses face a heavy psychological burden. This can cause significant anxiety and affect their psychological condition. This study aims to determine the effectiveness of psychoeducation and self-counseling in reducing anxiety in adolescents who experience role burden. The method used is a case study with a comprehensive psychiatric nursing care approach. The participant in the study was a 19-year-old female adolescent who experienced anxiety symptoms due to her role as a caregiver for parents with advanced cancer. This therapy was carried out for six sessions from March 10-22, 2025 with different topics at each meeting. Counseling and education topics include anxiety, managing negative thoughts, time management, relaxation techniques and self-evaluation and reflection. The effectiveness of therapy was measured using the Generalized Anxiety Disorder (GAD-7) and Self-Reporting Questionnaire (SRQ-20) questionnaires. Based on the results of the analysis and discussion, it shows a decrease in the GAD-7 score from 14 (moderate anxiety) to 3 (minimal anxiety) and a decrease in the SRQ-20 score from 9 to less than 6, which indicates no psychological disorders. In addition, the Client showed the ability to apply coping strategies independently, increased emotional control, and improvements in psychological well-being. The assessment of nursing care and the nursing problems were anxiety. Psychoeducation and independent counseling have proven effective in reducing anxiety in adolescents with role burdens. Development and implementation of similar interventions are needed in a wider scope to support the mental health of adolescents, especially those facing the burden of the role as caregivers.